Alat Pengusir Hama Burung Otomatis Berbasis Arduino (Atmega328 ) Menggunakan Sensor PIR (Passive Infra Red) - Odi Frastiya; Indra Roza; Agus Almi Nst (Universitas Medan Area, 2026)
Bird pests are a threat to agricultural crops, especially rice, corn, and fruit crops. This study designs an automatic bird repellent device based on Arduino (ATMega328) with a PIR (Passive Infrared) sensor to detect bird movement. When the PIR sensor detects birds, Arduino activates the sound module through a speaker to repel them. This device is designed to be energy efficient and works well in various weather conditions. Testing for 7 days in agricultural land showed the effectiveness of the device, with a significant decrease in the number of birds from an average of 30 birds per day on the first day to 5 birds per day on the seventh day. In addition, this device has low power consumption, around 0.5 kWh per day, which shows high efficiency in energy use.